STUDYING THE EFFECT OF BENZENE ON THE LEVEL OF A NUMBER OF VARIABLES AND PERCENTAGE OF FATTY ACIDS FOR WORKERS IN GAS STATIONS IN MOSUL - Noor A. Abd Al-Jabbar , Reem N. Alsawaf , Ebtehag Z. Sulyman , (Chelonian Research Foundation, 2024)
This study included the estimation of a number of biochemical variables related to antioxidants and the percentage of fatty acids. Glutathione(GSH), manoaldehyde (MDA), and the total capacity of antioxidants (TAC)in the blood serum of men who work at gas stations in the city of Mosul / Iraq. The workers were selected so that they did not suffer from any apparent disease (heart disease / diabetes / blood pressure) and were exposed on a daily basis to benzene and petroleum product pollutants, and the results of these variables were compared with a group of men of the same ages who do not work in the field of petroleum products. In this study, the percentage of fatty acids of different types (saturated and unsaturated) in the three parts of blood serum was measured: triglycerides(TG), phospholipids(PL), and cholesterol esters(CE). The results showed that there were significant differences in the level of biochemical variables and the percentage of fatty acids between the group of workers and the control group, which indicates the presence of an effect of gasoline and oil pollutants on the health of workers in this field. Keywords: GSH, MDA,TAC, gasoline, fatty acids , gas stations